Bismuth doping of induction furnace synthesized Mg2Si, Mg2Sn and Mg2Ge thermoelectric compounds. (May 2020) - Cahana, Meital; Gelbstein, Yaniv
Abstract: Silicides and especially Mg2 X (X = Si, Sn, Ge) are considered as attractive thermoelectric materials, which are capable of an efficient heat to electricity energy conversion. They have low density, abundant and affordable raw constituents, and good mechanical properties. Yet, the synthesis of such Mg- based compounds is usually very challenging due to the reactivity, volatility and oxidation tendency of Mg. These challenges led many of the researchers exploring these materials, to low temperature synthesis routes, where, the most common is a solid-state mechanical alloying, using ball milling. In such synthesis approaches, Mg volatility was compensated upon the introduction of excess Mg into the source materials, beyond the stoichiometric composition. In the current research a novel synthesis route based on an induction melting in a closed Ta chamber is proposed. Using this technique undoped and Bi-doped Mg2 X (X = Si, Sn, Ge) compounds were synthesized and analyzed. Phase separation into Mg2 X- and Mg3 Bi2 -rich phases was observed for the Bi-doped compositions, with an associated significant reduction of the lattice thermal conductivity. Highlights: a novel synthesis route based on an induction melting in a closed Ta chamber of Mg2 X (X = Si, Sn, Ge) is proposed. Using this technique undoped and Bi-doped compounds were synthesized and analyzed. Phase separation into Mg2 X- and Mg3 Bi2 - rich phases was observed for the Bi-doped compositions.